New Congressional Climate Change Task Force Calls on President to Use Administrative Authority. (5th February 2013) - Showstack, Randy
Abstract : Spurred by U.S. congressional inaction on climate change and by President Barack Obama's comments on the topic in his 21 January inaugural address, several Democratic members of Congress announced at a Capitol Hill briefing the formation of a bicameral task force on climate change. In addition, they have called on the president to use his administrative authority to deal with the issue.